Challenges of Follow-up in Guidance and Counseling Service: Perspective from Guidance and Counseling Service - Mudrikah, Syifa; Suherman, Uman (citeus, 2025)
This research examines the difficulties encountered in the implementation of follow-up guidance and counseling services, with a particular focus on the perspectives of school counselors. For the research methodology, a qualitative case study approach was adopted, along with semi-structured interview techniques. The findings indicate that the implementation of the follow-up stages of guidance and counseling is hindered by the absence of evaluation, supervision, and reporting, as well as the lack of support from the school. This can be identified as the primary obstacle to the implementation of follow-up. In light of these findings, this study offers a comprehensive examination of the aforementioned challenges and proposes strategies for enhancement.